Psychiatric symptoms may contribute to poor quality of life in adolescents with migraine. Issue 6 (20th September 2013) - Paschoal, Joelma Karin Sagica Fernandes; Lin, Jaime; Pinho, Ricardo Silva; Andreoni, Solange; Minett, Thais Soares Cianciarullo; Vitalle, Maria Sylvia de Souza; Fisberg, Mauro; Peres, Mario Fernando Prieto; Vilanova, Luiz Celso Pereira; Masruha, Marcelo Rodrigues
Abstract Background The impact of migraine on quality of life (QOL) can be aggravated by other comorbid factors. The aim of the present study was to assess the differences in the QOL of adolescents with chronic migraine, episodic migraine, and healthy adolescents, and whether the differences in QOL among the diagnostic groups were associated with the presence of self‐reported psychiatric symptoms, such as depression and anxiety. Methods A total of 157 adolescents (aged 15–19 years old) were included in the study. Fifty patients had episodic migraine, 56 patients suffered from chronic migraine, and 51 healthy adolescents were controls. All of the participants responded to a detailed headache questionnaire, the Medical Outcomes Trust 36‐Item Short‐form Health Survey, the State–Trait Anxiety Inventory and the Beck Depression Inventory. Results Chronic migraine patients showed a significantly lower QOL than the control subjects in five dimensions of the Medical Outcomes Trust 36‐Item Short‐form Health Survey, and lower QOL than the episodic migraine patients in four dimensions. High levels of self‐reported depressive symptoms were associated with lower QOL in five dimensions and high levels of self‐reported anxiety were associated with lower QOL in four dimensions. Conclusions The QOL of adolescent migraine sufferers may be aggravated not only by migraine but also by other factors, such as anxiety and depressive symptoms, which may contribute to the poor QOL in adolescents suffering from migraine.